Evident and epistemic American New Balance and Segway logo: a forensic linguistic study - Jauhar Helmie; Dadang Suganda; Heriyanto Heriyanto (Fakultas Seni Rupa dan Desain ITB, 2020)
The fact that language changes is inevitably touches aspects related to the law especially in implementing the task of being a linguist to deal with cases of duplication. Armed with knowledge of the symptoms of language change, a forgery case can be explained and explained so that justice is revealed. This paper aims to reveal how cases of logo and brand forgery can be revealed through linguistic studies by using forensic and visual studies. The writer will also discuss the rhetorical effects related to the underlying ambiguities between a purely evidential semiotics of the investigated strategies. The method used is descriptive qualitative with document analysis. This method explains in detail the actual state of data and data retrieval. The results found that the 2 data are linguistically and visually duplicate the original logo. Some fake products use the same language as the original product logo, but the copycat uses a language style that is more general and acceptable in the target community. In conclusion, phonological and visual analysis found similarities in the use of original brand consonants and vowels, as well as visualization of the type and size of letters appearing to imitate, deceive, and confusing customers.